The Influence of Price Perception and Service Quality on Customer Satisfaction of Maxim Application - Putra, Haris Satria; Wartiningsih , Endah; Anggraeni, Anggun Putri; Sofa, Nidia; Firdaus, Risya Zahrotul; Latianingsih, Nining (Poltanesa, 2024)
This study aims to analyze the influence of price perception and service quality on Customer satisfaction with the Maxim online transportation application in Depok City. With the rapid growth of online transportation in the Jabodetabek area, particularly in Depok, Maxim has become one of the preferred service providers due to its competitive pricing and numerous promotions. Based on previous research, factors such as service quality, price, and employee service have been shown to positively affect customer satisfaction. In the increasingly competitive online transportation industry, Customer satisfaction is a crucial factor for success. This study focuses on Maxim Customers in Depok, who are identified by their yellow helmets and jackets. According to data from the Central Bureau of Statistics of Depok City in 2020, the city has a population of over 2 million, but there is still limited research on Customer perceptions of Maxim's services in this area. This research uses a quantitative method with a purposive sampling approach, targeting male and female respondents aged 17 to 30 who have used Maxim’s services at least three times, with a sample of 100 respondents, and using the SmartPLS version 4 program. The results indicate that price perception has a positive and significant effect on Customer satisfaction, with a P-value of 0.001 < 0.05 and a path coefficient of 0.324 or 32.4%. Additionally, service quality is also proven to significantly influence Customer satisfaction, with a P-value of 0.000 < 0.05 and a path coefficient of 0.590 or 59%. These findings indicate that both variables—price perception and service quality—play important roles in determining the satisfaction level of Maxim Customers in Depok City. Therefore, online transportation companies are expected to continuously improve service quality and maintain competitive pricing to ensure customer satisfaction amid fierce competition.